2021
DOI: 10.2196/27544
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Virtual Reality Simulator for Tendon Repair Training: Randomized Controlled Trial

Abstract: Background Virtual reality (VR) simulators have become widespread tools for training medical students and residents in medical schools. Students using VR simulators are provided with a 3D human model to observe the details by using multiple senses and they can participate in an environment that is similar to reality. Objective The aim of this study was to promote a new approach consisting of a shared and independent study platform for medical orthopedic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Accumulating evidence suggested that patients with PD-L1 expression in tumor cells and stromal immune cells are more likely to respond to chemotherapy and immunotherapy and exhibit better prognosis [9,[45][46][47]. Previous study showed that hypoxia could induce high expression of PD-L1 on MDSCs and macrophages in tumor microenvironment, then suppresses the immune system to evade immune attack [48][49][50]. In our study, the expression of immune checkpoint markers was notably decreased in the high-risk group, which meant that the hypoxia-immune status in tumor microenvironment may affect the response to the immune checkpoint inhibitors (ICIs) therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggested that patients with PD-L1 expression in tumor cells and stromal immune cells are more likely to respond to chemotherapy and immunotherapy and exhibit better prognosis [9,[45][46][47]. Previous study showed that hypoxia could induce high expression of PD-L1 on MDSCs and macrophages in tumor microenvironment, then suppresses the immune system to evade immune attack [48][49][50]. In our study, the expression of immune checkpoint markers was notably decreased in the high-risk group, which meant that the hypoxia-immune status in tumor microenvironment may affect the response to the immune checkpoint inhibitors (ICIs) therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the diversification of virtual simulators/platforms/systems used in undergraduate medical education, we found that 48 (52%) studies ( 18 , 22 , 23 , 27 31 , 33 35 , 37 39 , 42 , 44 48 , 50 , 52 , 54 , 57 67 , 71 , 72 , 75 , 78 , 81 84 , 93 , 96 , 99 , 101 , 103 , 105 ) reported the immersive VR application, which is characterized by the use of VR equipment consisting of head-mounted displays (headsets or goggles) and/or hand controllers. This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education.…”
Section: Resultsmentioning
confidence: 84%
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations